EMOTIONAL SUPPORT FOR STAFF CARING FOR CHILDREN WITH MULTIPLE DISABILITIES - Petrova, Sevdalina (E-Journal VFU, 2025)
This article aims to highlight the impact of emotional burnout on professionals involved in the care of children with special educational needs. The topic is particularly relevant in the context of increasing demands on staff working in the social care sector, where high emotional strains, chronic stress and limited institutional support often lead to psychological and physical exhaustion. The theoretical part of the study examines leading models defining the nature, stages and contributing factors of burnout syndrome. Through the analysis of these paradigms, it aims not only to explain the phenomenon in its complexity, but also to outline possible prevention and intervention guidelines oriented towards improving the professional well-being of employees in this sensitive area.